Evaluation of the Characteristics and Application of SBS Composite-Modified Bitumen Materials in Low-Temperature Environments - Ren, Wenxiao; Li, Ping (Engineering Transactions, 2026)
To improve the resistance of bitumen pavements to low-temperature cracking, this study proposes a composite-modified bitumen based on styrene-butadiene-styrene (SBS) copolymer and crumb rubber. This modified bitumen is also tested for its performance in a low-temperature environment. The test results indicate that, after aging and freeze-thaw cycles (FTCs), the creep rates (CRs) of both SBS-modified bitumen and the SBS/crumb rubber composite-modified bitumen decreased. However, the CR of the SBS/crumb rubber composite-modified bitumen was constantly lower than that of the SBS-modified bitumen. For example, at −12 °C, the CRs of the aged SBS-modified bitumen and SBS/crumb rubber composite-modified bitumen were 0.44 and 0.37, respectively. When the bitumen mixtures underwent FTCs and aging, their fracture energy densities (FEDs) drastically decreased. Nevertheless, the FEDs of the SBS/crumb rubber composite-modified bitumen mixtures were higher than those of the SBS-modified bitumen mixtures. These results indicate that the composite-modified bitumen with SBS/crumb rubber has good rheological properties and freeze-thaw resistance, thereby effectively ensuring the low-temperature performance of bitumen pavements.